Method for manufacturing laminate, method for manufacturing coated object, method for manufacturing bonded structure, thermal transfer sheet, and laminate

By using a release film without yield point and a thermal transfer sheet with a thermal transfer layer, the bond strength problem between the resin material and the coating is solved, and efficient and low-cost complex shape surface coating treatment is achieved, ensuring high bond strength and appearance quality.

JP7628797B2Active Publication Date: 2025-02-12NITTO DENKO CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020175634
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-24
Filing Date
2020-10-19
Publication Date
2025-02-12
Estimated Expiration
2040-10-19

AI Technical Summary

Technical Problem

The prior art When manufacturing a lightweight and high impact resistance resin material, it is difficult to achieve high bond strength with the coating, especially on complex shape surfaces, and traditional surface treatment methods lead to low production efficiency, high cost, and prone to wrinkles and surface defects.

Method used

A thermal transfer sheet is used, which contains a release film without yield points and a thermal transfer layer, which is bonded to the surface of the resin material by heating and bonding, ensuring good follow-up in the three-dimensional shape, avoiding wrinkles and forming a uniform coating during the bonding process.

Benefits of technology

High bond strength and uniformity of coating on complex shape surfaces are achieved, production efficiency is improved, costs are reduced, wrinkles and surface defects are avoided, and resin materials with excellent appearance are formed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628797000003
    Figure 0007628797000003
  • Figure 0007628797000004
    Figure 0007628797000004
  • Figure 0007628797000005
    Figure 0007628797000005
Patent Text Reader

Abstract

To provide a method of manufacturing a laminate whereby it is possible to form a laminate that has excellent followability to a three-dimensional shape, prevents a plane surface part and a curved surface part from becoming wrinkled, and has an excellent appearance, it is possible to give high adhesion and coating adhesion, and it is possible to integrally mold a heat transfer layer and a resin member when forming the laminate, and provide a method of manufacturing a coated object and a method of manufacturing a junction structure using the laminate formed by the method of manufacturing the laminate.SOLUTION: The present invention relates to a method of manufacturing a laminate, the method comprising a lamination step for laminating, on at least a part of a surface of a resin member, a heat transfer layer side of a heat transfer sheet including a release sheet and the heat transfer layer by heat bonding, wherein the release sheet has no yield point in a stress-strain curve measured by a tensile test at a molding temperature Tβ°C in the lamination step and has an elongation at breakage of 100% to 600%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a laminate, a method for producing a coated article, a method for producing a bonded structure, a thermal transfer sheet, and a laminate. [Background technology]

[0002] In recent years, lightweight and impact-resistant resins have been used for components of transportation equipment such as railroad cars, aircraft, ships, and automobiles, electronic devices, housing equipment, etc., and adherends made of various materials are bonded to the surfaces of these resin members. In addition, coating films having various functions may be formed on the resin members. When a resin member is bonded to an adherend such as a metal or another resin, sufficient adhesive strength is required. When a coating film is applied to a resin member, various resins are used as base polymers for the coating film, and in order to prevent the coating film from peeling off, it is necessary to strengthen the adhesion between the resin member and the coating film. In addition, the shapes of the coating film are also various, and it is also required to be able to handle complex shapes.

[0003] However, depending on the type of resin member and adherend, the adhesive may not be compatible with the resin member, and sufficient adhesive strength may not be obtained even if a conventional adhesive or adhesive sheet is used. In addition, when a coating is applied directly to a resin member, depending on the type of resin member and coating film, compatibility may be poor, and sufficient adhesive strength between the resin member and coating film may not be obtained, resulting in problems such as unevenness and peeling of the coating film.

[0004] Known means for obtaining sufficient adhesive strength include primer treatment (e.g., Patent Document 1), in which a primer solution is applied to the surface of a molded resin part, and various surface treatment methods such as sandblasting, corona treatment, and plasma treatment as pretreatment.

[0005] Furthermore, one of the means for imparting sufficient adhesive strength to a resin member is a technique that uses a surface-modified sheet. For example, Patent Document 2 describes a surface-modified sheet that can be thermally transferred using the heat of thermoforming of a resin member to impart sufficient adhesive strength. A flat-plate transfer method is described here. Patent Document 3 describes an integrated molding technique in which an adhesive layer is transferred to a resin substrate by in-mold injection molding. In this technique, a laminate having a substrate layer, an adhesive sheet layer, and a release sheet layer in this order is molded in advance in a mold having the same shape as that used for the subsequent integrated injection molding to form a laminated molded body, which is then used for the subsequent integrated injection molding, so that the resin is inserted without any gaps during injection molding, and a molded product that conforms to the shape of the mold is obtained. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2000-226536 A [Patent Document 2] JP 2017-128722 A [Patent Document 3] JP 2019-51687 A Summary of the Invention [Problem to be solved by the invention]

[0007] In the conventional surface treatment method as described in Patent Document 1, a surface treatment step and a drying step must be provided, which results in a problem of reduced productivity. Furthermore, when molding a resin part using a mold, it is necessary to use a release agent, but this release agent contaminates the surface of the resin part, making it impossible to form a coating film of sufficient strength on the surface of the resin part by primer treatment. Therefore, a cleaning process or a polishing process is required to remove the release agent. As a result, there is a problem of increased costs, such as capital investment and running costs for carrying out these processes.

[0008] On the other hand, according to the film in-mold molding as described in Patent Documents 2 and 3, the surface of the resin member can be treated without using a release agent during molding. However, depending on the molding temperature, wrinkles may occur in the release sheet during molding, and the wrinkles may be transferred to the surface of the thermal transfer layer, impairing the appearance of the resulting laminate. In addition, attempts have been made to impart a design layer using film in-mold molding, but the ability of the release sheet or the design base material to follow the three-dimensional shape of the mold is an issue. Furthermore, the surface-treated resin member may be painted or bonded to an adherend, and therefore high adhesive strength and high paint adhesion to the adherend are required.

[0009] In view of the above problems, the present invention aims to provide a method for producing a laminate that has good conformability to three-dimensional shapes, prevents the occurrence of wrinkles on flat and curved surfaces, and is capable of forming a laminate with excellent appearance, and that can impart high adhesion and paint adhesion, and further allows integral molding of a thermal transfer layer and a resin member when forming the laminate, as well as a method for producing a coated article and a method for producing a bonded structure using the laminate obtained by the laminate production method. Another object of the present invention is to provide a thermal transfer sheet suitable for the laminate production method, and a laminate including the thermal transfer sheet. [Means for solving the problem]

[0010] The present inventors have conducted extensive research to solve the above problems, and have found that by heat-attaching a thermal transfer sheet having a release sheet with tensile properties that have no yield point and a specific range of elongation at break to a resin member, a laminate can be formed that exhibits high adhesive strength and high paint adhesion, has good conformability to three-dimensional shapes, prevents wrinkles from occurring on flat and curved surfaces, and has excellent appearance, and that the thermal transfer layer and the resin member can be integrally molded when forming the laminate, thereby completing the present invention.

[0011] That is, the present invention relates to the following [1] to

[16] . [1] A method for producing a laminate, comprising: a lamination step of laminating a thermal transfer layer side of a thermal transfer sheet having a release sheet and a thermal transfer layer to at least a part of a surface of a resin member by heat adhesion, The method for producing a laminate, wherein the release sheet has no yield point and a breaking elongation of 100 to 600% in a stress-strain curve measured by a tensile test at a molding temperature Tβ°C in the lamination step. [2] The method for producing a laminate according to [1], wherein the release sheet has no yield point and a breaking elongation of 150 to 600% in a stress-strain curve measured by a tensile test at a molding temperature Tβ°C in the lamination step. [3] The method for producing a laminate according to [1] or [2], wherein the release sheet has a stress-strain curve measured by a tensile test at the forming temperature Tβ°C, in which a slope of a plastic deformation region after 50% elongation from an inflection point between an elastic deformation region and a plastic deformation region is 0 to 50. [4] The method for producing a laminate according to any one of [1] to [3], wherein the thermal transfer layer has an average thickness of 0.1 μm to 50 μm. [5] The method for producing a laminate according to any one of [1] to [4], wherein in the lamination step, the heat bonding is carried out by heat pressing. [6] A method for producing a coated article, comprising a coating film forming step of peeling off the release sheet from a laminate obtained by the method for producing a laminate according to any one of [1] to [5], and forming a coating film on the exposed thermal transfer layer. [7] A method for producing a bonded structure, comprising a bonding step of peeling off the release sheet from a laminate obtained by the method for producing a laminate according to any one of [1] to [5], and bonding an adherend onto the exposed thermal transfer layer via an adhesive layer. [8] A release sheet and a thermal transfer layer are provided, The release sheet is a thermal transfer sheet which has no yield point and has a breaking elongation of 100 to 600% in a stress-strain curve measured by a tensile test at Tα° C. represented by the following formula (1). Tα℃ = glass transition temperature of release sheet (Tg)℃ + 70℃ (1) [9] The thermal transfer sheet according to [8], wherein the release sheet has no yield point and a breaking elongation of 150 to 600% in a stress-strain curve measured by a tensile test at Tα°C represented by the formula (1).

[10] The thermal transfer sheet according to [8] or [9], wherein in a stress-strain curve measured by a tensile test at Tα°C, the slope of the plastic deformation region after 50% elongation from the inflection point between the elastic deformation region and the plastic deformation region is 0 to 50.

[11] The thermal transfer sheet according to any one of [8] to

[10] , wherein the thermal transfer layer has an average thickness of 0.1 μm to 50 μm.

[12] The thermal transfer sheet according to any one of [8] to

[11] , wherein the thermal transfer layer contains a polymer component, and the polymer component contains at least one of a polymer having a non-polar unit and a polar unit, and a polymer in which a portion of a polymer composed of a non-polar unit is modified with a polar unit having a polar group.

[13] The thermal transfer sheet according to

[12] , wherein the polymer component contains at least one selected from the group consisting of a methoxymethyl group-containing polymer, a hydroxyl group-containing polymer, a carboxyl group-containing polymer, and an amino group-containing polymer.

[14] The thermal transfer sheet according to any one of [8] to

[13] , which is applied by heating.

[15] [8] to

[14] , and a resin member laminated on the thermal transfer layer side of the thermal transfer sheet.

[16] The laminate according to

[15] , wherein the resin member is a prepreg. Effect of the Invention

[0012] According to one embodiment of the method for producing a laminate of the present invention, it is possible to form a laminate that has good conformability to three-dimensional shapes, prevents the occurrence of wrinkles on flat and curved surfaces, and has an excellent appearance. It is also possible to impart high adhesion and paint adhesion, and further, it is possible to integrally mold the thermal transfer layer and the resin member when forming the laminate. Furthermore, the laminate according to one embodiment of the present invention has excellent adhesive strength with coating films and adherends, is prevented from causing wrinkles, and can form a resin molded product with excellent appearance. According to the method for producing a coated article and a method for producing a bonded structure according to one aspect of the present invention, a coated article and a bonded structure having excellent strength and excellent appearance can be obtained. [Brief description of the drawings]

[0013] [Figure 1] 1 is a schematic cross-sectional view showing an example of a laminate in which a thermal transfer layer is provided on the surface of a resin member. [Diagram 2] FIG. 1 is a schematic cross-sectional view showing an example of a thermal transfer sheet. [Diagram 3] 1 is a schematic cross-sectional view showing a form in which the thermal transfer layer side of a thermal transfer sheet, which is a laminate of a release sheet and a thermal transfer layer, is placed on at least a part of the surface of a resin member. [Figure 4] FIG. 2 is a schematic cross-sectional view showing an example of a coated object. [Diagram 5] FIG. 1 is a schematic cross-sectional view showing an example of a joint structure. [Figure 6] FIG. 2 is a schematic perspective view of a bonded structure used in evaluating shear adhesive strength. [Figure 7] 1 is a stress-strain curve measured by a tensile test at a molding temperature Tβ° C. for the release sheet of Example 2. [Figure 8] 1 is a stress-strain curve measured by a tensile test at a molding temperature Tβ° C. for the release sheet of Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present invention will be described in detail.

[0015] <Method of manufacturing laminate> A method for producing a laminate according to an embodiment of the present invention includes a lamination step of laminating a thermal transfer sheet having a release sheet and a thermal transfer layer on at least a part of a surface of a resin member by heat adhesion, wherein the release sheet has no yield point and has a breaking elongation of 100 to 600% in a stress-strain curve measured by a tensile test at a molding temperature Tβ°C in the lamination step.

[0016] [Thermal transfer sheet] The thermal transfer sheet used in the laminate manufacturing method according to the embodiment of the present invention includes a release sheet and a thermal transfer layer. Here, since the thermal transfer layer in the thermal transfer sheet is in the form of a sheet, it can be integrally molded by placing it on the surface of the member and heating it, rather than applying it by coating. Therefore, it is possible to prevent unevenness due to repelling and the like, and form a thermal transfer layer with a uniform thickness on the surface of the member. In addition, when applying the thermal transfer layer to a part of the surface of the member, it is possible to suppress a decrease in yield due to overflow and the like.

[0017] [Release sheet] In the method for producing a laminate according to an embodiment of the present invention, the release sheet in the thermal transfer sheet has no yield point and a breaking elongation of 100 to 600% in a stress-strain curve measured by a tensile test at a molding temperature Tβ°C in the lamination step. In addition, tensile properties such as the presence or absence of a yield point, the elongation at break, and the slope of the plastic deformation region after 50% elongation from the inflection point between the elastic deformation region and the plastic deformation region described below can be adjusted by the configuration of the release sheet, the materials used, or a combination thereof.

[0018] (Tensile test) The tensile test is carried out using a tensile tester equipped with a thermostatic chamber under the following test conditions. Test equipment: Shimadzu AG-X 200N Sample piece: Use a dumbbell No. 1 piece punched out. Tensile speed: 200mm / min Between marked lines: 40mm Preheating: Place the sample between the chucks in a thermostatic chamber set at Tβ℃, close the door, and once the temperature inside the chamber has stabilized (after about 10 minutes), start the test.

[0019] (yield point) When a stress-strain curve is plotted using the above tensile test at Tβ°C, with the horizontal axis representing elongation (%) and the vertical axis representing tensile stress (MPa), an inflection point usually appears as the sample transitions from the elastic region to the plastic region. At this time, a maximum point appears on the stress-strain curve, and the stress drops once and then rises again; this phenomenon is called the necking phenomenon, and this maximum point on the stress-strain curve is called the yield point. Here, when the release sheet does not have a yield point in the stress-strain curve measured by a tensile test at a molding temperature Tβ°C, local elongation of the release sheet during molding is suppressed, so that bending or tearing does not occur not only in the flat parts but also in the curved parts that tend to elongate locally, and curved surface conformability is good. Therefore, the occurrence of wrinkles is effectively prevented not only in the flat parts but also in the curved parts.

[0020] (Elongation at break) In addition, in the stress-strain curve measured by the above tensile test at Tβ° C., the point at which the release sheet breaks is taken as the breaking point, and the elongation value at that time is taken as the breaking point elongation. Here, when the elongation at break is 100 to 600%, uniform elongation is obtained, so that it becomes possible to follow a three-dimensional shape. If the elongation at break is less than 100%, the elongation is insufficient, so that wrinkles may occur or the sheet may break. If the elongation at break is more than 600%, there is a risk that a sufficient thickness of the thermal transfer layer cannot be obtained after molding. The elongation at break is preferably 110 to 500%, more preferably 120 to 400%, and even more preferably 150 to 400%. In one embodiment, the elongation at break may be 150 to 600%.

[0021] In addition, in a stress-strain curve measured by the above tensile test at Tβ° C., the gradient of the plastic deformation region after 50% elongation from the inflection point between the elastic deformation region and the plastic deformation region of the release sheet is preferably 0 to 50. The inclination is preferably 0 to 50, since uniform elongation can be obtained over a wider range, and better three-dimensional conformability can be obtained. If the inclination is smaller than 0, localized elongation may occur. If the inclination is larger than 50, sufficient elongation may not be obtained during molding, and wrinkles may occur. The inclination is more preferably 5 to 40, and even more preferably 10 to 30. Here, since there is an inflection point when transitioning from the elastic region to the plastic region, the slope a can be calculated using the following formula (i), starting from the point 50% after the inflection point. a = ((S2-S1) / (E2-E1)) × 100 (i) E1: (inflection point growth +50) (%) E2: ((inflection point growth +50) +30)(%) S1: Stress (MPa) at (elongation at inflection point + 50) (%) S2: Stress (MPa) at ((elongation at inflection point + 50) + 30) (%)

[0022] Examples of release sheets that can be used for the above thermal transfer sheet include unstretched polyamide 6, unstretched polyamide 66, biaxially oriented polyamide 6, biaxially oriented polyamide 66, biaxially oriented polypropylene, biaxially oriented polyethylene terephthalate, biaxially oriented polybutylene terephthalate, easily molded polyethylene terephthalate, cast molded polytetrafluoroethylene, unstretched extruded tetrafluoroethylene-ethylene copolymer (ETFE), unstretched extruded tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), unstretched extruded tetrafluoroethylene-hexafluoropropylene copolymer (FEP), and laminates having these as the main layer. From the viewpoints of ease of handling and prevention of breakage, the thickness of the release sheet is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 20 μm or more, and even more preferably 30 μm or more. From the viewpoint of conformability to a three-dimensional shape, the thickness is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 100 μm or less. If necessary, the surface of the release sheet facing the thermal transfer layer or both surfaces of the release sheet may be subjected to a release treatment using an appropriate release treating agent such as silicone.

[0023] [Thermal transfer layer] The thermal transfer layer (which may be a material for the thermal transfer layer) preferably contains a polymer component, and more preferably contains at least one of a polymer having a polar unit having a nonpolar unit and a polar group, and a polymer in which a part of a polymer composed of a nonpolar unit is modified with a polar unit having a polar group. The content of the polymer component in the thermal transfer layer is preferably 50% to 100% by mass, more preferably 70% to 100% by mass, even more preferably 90% to 100% by mass, particularly preferably 92% to 100% by mass, and most preferably 95% to 100% by mass.

[0024] Examples of the non-polar unit in the polymer component include an aliphatic hydrocarbon unit, an aromatic hydrocarbon unit, an alicyclic hydrocarbon unit, etc. The number of carbon atoms in the non-polar unit is preferably 2 to 40, more preferably 3 to 30, and further preferably 4 to 20. The non-polar unit may be of only one type, or of two or more types.

[0025] Examples of the polar unit having a polar group in the polymer component include an epoxy group, a carboxyl group, a nitrile group, an amide group, an ester group, a hydroxyl group, an acid anhydride, and a silanol group. Examples of the polar unit having such a polar group include a glycidyl methacrylate unit, a vinyl acetate unit, an acrylonitrile unit, an amide unit, a (meth)acrylic acid ester unit, a hydroxyethyl (meth)acrylate unit, and a maleic anhydride unit. The polar unit may be of only one type, or of two or more types.

[0026] The polymer component that may be contained in the thermal transfer layer (which may be the material of the thermal transfer layer) may be at least one selected from a methoxymethyl group-containing polymer, a hydroxyl group-containing polymer, a carboxyl group-containing polymer, and an amino group-containing polymer.

[0027] Such polymer components that may be included in the thermal transfer layer (which may be the material of the thermal transfer layer) are preferably addition type hardeners, and more preferably addition type hardeners that react with epoxy groups.

[0028] Examples of the methoxymethyl group-containing polymer include methoxymethylated polyamide resins. The methoxymethyl group-containing polymer may be a commercially available product, such as "Fine Resin" (registered trademark) FR-101, FR-104, FR-105, EM-120, and EM-220 series (manufactured by Lead City Corporation). The methoxymethyl group-containing polymer may be one type or two or more types.

[0029] In order to further exert the effects of the present invention, the methoxymethyl group-containing polymer preferably has a weight average molecular weight (Mw) of 1000 to 1000000, more preferably 3000 to 500000, still more preferably 5000 to 100000, particularly preferably 7000 to 70000, and most preferably 10000 to 50000. The method for measuring the weight average molecular weight (Mw) will be described later.

[0030] Examples of the hydroxyl group-containing polymer include hydroxyl group-containing acrylic polymers. The hydroxyl group-containing polymer may be a commercially available product, such as "ARUFON (registered trademark) UH-2000 series" (manufactured by Toagosei Co., Ltd.). The hydroxyl group-containing polymer may be one type or two or more types.

[0031] In order to more effectively exert the effects of the present invention, the hydroxyl group-containing polymer has a weight average molecular weight (Mw) of preferably 500 to 1,000,000, more preferably 700 to 500,000, even more preferably 1,000 to 100,000, particularly preferably 1,500 to 70,000, and most preferably 2,000 to 50,000. The method for measuring the weight average molecular weight (Mw) will be described later.

[0032] Examples of the carboxyl group-containing polymer include a carboxyl group-containing acrylic polymer and a carboxyl group-containing acrylic oligomer. The carboxyl group-containing polymer may be a commercially available product, such as "ARUFON (registered trademark) UC-3000, UC3510, UC3080 series" (manufactured by Toagosei Co., Ltd.). The carboxyl group-containing polymer may be one type or two or more types.

[0033] In order to more effectively exert the effects of the present invention, the carboxyl group-containing polymer has a weight average molecular weight (Mw) of preferably 500 to 1,000,000, more preferably 700 to 500,000, even more preferably 1,000 to 100,000, particularly preferably 1,500 to 70,000, and most preferably 2,000 to 50,000. The weight average molecular weight (Mw) was measured using polystyrene equivalent molecular weight measured by GPC.

[0034] As the amino group-containing polymer, any appropriate polymer may be used as long as it contains an amino group (-NH2) and does not impair the effects of the present invention. As the amino group-containing polymer, a commercially available product may be used. The amino group-containing polymer may be one type or two or more types. The thermal transfer layer (which may be the material of the thermal transfer layer) may contain at least one selected from a tertiary amine-containing compound and a strong acid.

[0035] Such tertiary amine-containing compounds and strong acids that may be contained in the thermal transfer layer (which may be the material of the thermal transfer layer) are preferably catalytic curing agents, and more preferably catalytic curing agents that react with epoxy groups.

[0036] Examples of the tertiary amine-containing compound include imidazole derivatives and polyethyleneimine. As the tertiary amine-containing compound, commercially available products may be used. Examples of such commercially available products include the imidazole derivative "Curezol" series (imidazole-based epoxy resin curing agent, manufactured by Shikoku Chemical Industry Co., Ltd.) and the like, and the polyethyleneimine "Epomin" (registered trademark) series (manufactured by Nippon Shokubai Co., Ltd.) and the like. The tertiary amine-containing compound may be one type or two or more types.

[0037] Examples of strong acids include trifluoroborane, ionic liquids, and Nafion. Examples of ionic liquids include BF3-C2H5NH2 and HMI-PF6. As the strong acid, commercially available products may be used. The strong acid may be one type or two or more types.

[0038] In the embodiment of the present invention, the thermal transfer layer preferably has an average thickness of 0.1 μm to 50 μm. Pinholes on the surface of a part impair the appearance of the resin part obtained by subsequent painting, etc. In an embodiment of the present invention, the thermal transfer layer has an average thickness of 0.1 μm to 50 μm, which is preferable because it can fill in irregularities such as pinholes on the surface of the part and provide a more excellent appearance. Furthermore, when the thickness of the thermal transfer layer is 0.1 μm to 50 μm, the thermal transfer layer flows appropriately during thermoforming, which provides the release sheet with slidability and improves conformability to the shape of the mold, which is preferable. The average thickness of the thermal transfer layer is more preferably 0.5 μm or more, and even more preferably 0.7 μm or more, from the viewpoint of filling irregularities such as pinholes on the surface of the member and obtaining a better appearance. Also, from the viewpoint of adhesive strength, the average thickness of the thermal transfer layer is more preferably 40 μm or less, and even more preferably 20 μm or less. The thickness of the thermal transfer layer can be measured by measuring the thickness of the thermal transfer sheet with a dial thickness gauge (e.g., Peacock GC-9), measuring the thickness of the release sheet from which the thermal transfer layer has been removed at that location, and measuring the thickness of the release sheet, taking the difference as the thickness of the thermal transfer layer. The average thickness of the thermal transfer layer is the average value of measurements taken at 10 points.

[0039] (Lamination process) In the method for producing a laminate according to an embodiment of the present invention, the thermal transfer layer side of the thermal transfer sheet is laminated on at least a part of the surface of a resin member, and heat adhesion is performed to produce a laminate. The heat adhesion may be carried out simultaneously with lamination of the thermal transfer sheet, or may be carried out after lamination of the thermal transfer sheet. By performing the surface treatment of the resin member in this manner, it is possible to impart sufficient adhesive strength to the resin member, and it is possible to manufacture the laminate with high productivity and low cost. The method for manufacturing the laminate can also be a method for treating the surface of the resin member (a method for surface treating a resin).

[0040] The resin contained in the resin member may be a thermoplastic resin or a thermosetting resin. Examples of thermoplastic resins include PP (polypropylene), PA (polyamide), PPE (polyphenylene ether), PPS (polyphenylene sulfide), PET (polyethylene terephthalate), PBT (polybutylene terephthalate), POM (polyacetal), PEEK (polyether ether ketone), PC (polycarbonate), PES (polyether sulfide), EP (epoxy), etc. Among these resins, thermoplastic resins that can advantageously exhibit the effects of the present invention include PPS (polyphenylene sulfide), PA (polyamide), PES (polyether sulfide), and EP (epoxy).

[0041] As the thermoplastic resin, fiber reinforced thermoplastic resin (FRTP) can be adopted. Examples of fiber reinforced thermoplastic resins (FRTP) include carbon fiber reinforced thermoplastic resins (CFRTP) and glass fiber reinforced thermoplastic resins (GFRTP). Examples of carbon fiber reinforced thermoplastic resins (CFRTP) include PPS-based carbon fiber reinforced thermoplastic resins, PA-based carbon fiber reinforced thermoplastic resins, PES-based carbon fiber reinforced thermoplastic resins, EP-based carbon fiber reinforced thermoplastic resins, and PP-based carbon fiber reinforced thermoplastic resins. Examples of glass fiber reinforced thermoplastic resins (GFRTP) include PPS-based glass fiber reinforced thermoplastic resins, PA-based glass fiber reinforced thermoplastic resins, and PP-based glass fiber reinforced thermoplastic resins.

[0042] Examples of the thermosetting resin include unsaturated polyester resin, vinyl ester resin, epoxy resin, melamine resin, phenol resin, urethane resin, polyisocyanate resin, polyisocyanurate resin, and polyimide resin.

[0043] Examples of the shape of the resin member include a plate having a flat surface, a plate having a curved surface, a sheet, and a film. The resin member has a thickness of, for example, 0.001 mm to 10 mm. The resin member may be a prepreg, which is made by impregnating a reinforcing material such as carbon fiber or glass fiber with a thermosetting resin mixed with an additive such as a curing agent, and then heating or drying it to a semi-cured state.

[0044] "At least a part of the surface of the resin member" means at least a part of all the surfaces of the resin member. For example, when the resin member is in the form of a plate, sheet, or film, it means a part of at least one of the surfaces, or the entirety of at least one of the surfaces.

[0045] When a thermoplastic resin is used as the resin in the resin member, in the production of the laminate, when the melting point of the thermoplastic resin is T1°C, a thermal transfer layer is provided on at least a part of the surface of the thermoplastic resin member, and heat bonding is preferably performed at a temperature of (T1-50)°C or higher. The temperature of this heat bonding is preferably (T1-50)°C to (T1+150)°C, more preferably (T1-25)°C to (T1+100)°C, even more preferably (T1-10)°C to (T1+75)°C, and particularly preferably (T1)°C to (T1+50)°C. By performing surface treatment of the resin member by the above-mentioned method with the heat bonding temperature, i.e., the molding temperature Tβ°C, within the above range, the interface between the thermal transfer layer and the thermoplastic resin member is melt-contacted and melt-mixed, and sufficient adhesive strength can be imparted to the thermoplastic resin member. Such impartation can be performed with high productivity and low cost.

[0046] When a thermoplastic resin is used as the resin in the resin member, a thermal transfer layer can be provided on the surface of the molten thermoplastic resin member after at least a part of the surface of the thermoplastic resin member is melted. By providing a thermal transfer layer on the molten surface of the thermoplastic resin member, the thermal transfer layer is melted and mixed by the heat of the surface of the thermoplastic resin member, and sufficient adhesive strength can be imparted to the thermoplastic resin member.

[0047] When a thermosetting resin is used as the resin in the resin member, in the manufacture of the laminate, when the curing temperature of the thermosetting resin is T2°C, it is preferable to provide a thermal transfer layer on at least a part of the surface of the thermosetting resin member and perform heat bonding at a temperature of (T2-50)°C or higher. The curing temperature is the peak temperature of the heat generation curve measured by DSC. The temperature of this heat bonding is preferably (T2-50)°C to (T2+50)°C, more preferably (T2-40)°C to (T2+40)°C, even more preferably (T2-30)°C to (T2+30)°C, and particularly preferably (T2-20)°C to (T2+20)°C. By setting the heat bonding temperature, i.e., the molding temperature Tβ°C, within the above range and performing surface treatment of the resin member by the above method, the interface between the thermal transfer layer and the thermosetting resin member is chemically bonded, and sufficient adhesive strength can be imparted to the thermosetting resin member. Such impartation can be performed with high productivity and low cost.

[0048] When the resin member is a prepreg, it is preferable to provide a mixed layer in which the prepreg and the thermal transfer layer are mixed between the prepreg and the thermal transfer layer. When the resin contained in the resin member is a thermosetting resin, a thermal transfer layer can be provided on the surface of the thermosetting resin member after at least a part of the surface of the thermosetting resin member is softened by heating. By providing a thermal transfer layer on the surface of the thermosetting resin member softened by heating, the thermal transfer layer is chemically bonded by the heat of the surface of the thermosetting resin member, and sufficient adhesive strength can be imparted to the thermosetting resin member.

[0049] The term "chemical bond" refers to a bond that can be achieved by forming a chemical covalent bond between the resin member and the material of the thermal transfer layer.

[0050] Examples of the heat-attaching method include oven heating, infrared heating, high-frequency heating, and heat pressing, with heat pressing (press molding) being preferred. The time for heat adhesion is preferably from 1 second to 10 minutes.

[0051] In the lamination step, the resin member may be laminated on the thermal transfer layer side of the thermal transfer sheet, and then molded by hot pressing. The hot press is, for example, a mode in which the thermal transfer layer side of the thermal transfer sheet is laminated on at least a part of the surface of a resin member in a molding machine (e.g., a press machine, etc.), and molding processing involving heating (e.g., integral molding by hot press) is performed. According to such a mode, the surface treatment of the resin member and molding processing of the resin member can be performed simultaneously, thereby providing high productivity and low cost.

[0052] In addition, a laminate having a thermal transfer layer on its surface can be obtained by peeling the release sheet from the laminate. The method for peeling the release sheet is not particularly limited, and may include peeling by hand or using dedicated peeling equipment.

[0053] The thermal transfer layer side of the thermal transfer sheet, which is a laminate of the release sheet and the thermal transfer layer, is placed on at least a part of the surface of the resin member, and after heat adhesion, the release sheet is preferably removed. By removing the release sheet in this manner, the thermal transfer layer is transferred to the surface of the resin member, and a laminate (sometimes referred to as a laminate member of the resin member and the thermal transfer layer) is obtained. As described above, it is preferable to provide a mixed layer between the resin member and the thermal transfer layer, in which the resin member and the thermal transfer layer are mixed.

[0054] By the above-mentioned manufacturing method, a thermal transfer layer 10 is provided on the surface of a resin member 100, and a laminate is obtained, as shown in Fig. 1. Note that, although the thermal transfer layer 10 is laminated on the surface of the resin member 100 in Fig. 1, it is preferable to provide a mixed layer (not shown) in which the resin member and the thermal transfer layer are mixed between the resin member 100 and the thermal transfer layer 10.

[0055] The thermal transfer sheet, which is a laminate of a release sheet and a thermal transfer layer, is a thermal transfer sheet 200, which is a laminate of a release sheet 20 and a thermal transfer layer 10, as shown in FIG.

[0056] In the manufacturing method of a laminate according to an embodiment of the present invention, the thermal transfer layer side of a thermal transfer sheet, which is a laminate of a release sheet and a thermal transfer layer, is placed on at least a portion of the surface of the resin member in a form in which the thermal transfer sheet 200 is placed on the surface of the resin member 100 such that the thermal transfer layer 10 side of the thermal transfer sheet 200 is the surface side of the resin member 100, as shown in FIG.

[0057] <Manufacturing method for coated items> In addition, the method for producing a coated article according to an embodiment of the present invention includes a coating film formation step of peeling off the release sheet of the laminate obtained by the above-mentioned method for producing a laminate and forming a coating film on the exposed thermal transfer layer. By the coating film forming step, a coated product having a coating film on at least a part of the surface of the laminate on the thermal transfer layer side can be obtained. As an example of the coated article, FIG. 4 shows a coated article 300 having a coating film 30 on the surface of the thermal transfer layer side of a laminate in which a thermal transfer layer 10 is provided on the surface of a resin member 100. Since the thermal transfer layer is formed using a sheet-like thermal transfer sheet rather than being applied to the surface of the resin member, it is possible to prevent unevenness due to repelling and the like. Therefore, the thermal transfer layer can be formed with a uniform thickness on the surface of the resin member, and the coating film can be applied with a uniform film thickness. In addition, by providing a thermal transfer layer on the surface of a resin member in a molten state, the thermal transfer layer is fused and mixed by the heat of the surface of the resin member, and since the adhesive strength between the thermal transfer layer and the resin member is high, a coating film with excellent adhesion can be formed. Furthermore, when forming a coated product, since the thermal transfer layer and the resin member can be integrally molded, a cleaning process using an organic solvent or a polishing process for removing the release agent before forming the coating film is not required, which is safe and reduces the environmental burden and work load.

[0058] The coating film is not particularly limited, and examples thereof include paint, a printed layer, a vapor deposition layer, a plating layer, etc. The material forming the coating film is not particularly limited, and examples thereof include compositions containing various polymers such as acrylic, urethane, epoxy, fluorine, polyester-melamine, alkyd-melamine, acrylic-melamine, acrylic-urethane, and acrylic-polyacid hardener. The thickness of the coating film is not particularly limited and is generally from 0.01 to 2000 μm, more preferably from 0.1 to 1000 μm, further preferably from 0.5 to 500 μm, and particularly preferably from 1 to 200 μm. There is no particular limitation on the method of applying the coating film, and common methods such as brush coating, roller coating, spray coating, various coater coating, etc. can be used, and the amount of coating is not particularly limited. In addition, the time and temperature for heating the coating film can be appropriately determined depending on the coating material used, the amount of coating, etc.

[0059] <Method of manufacturing bonded structure> Furthermore, the manufacturing method of the bonded structure according to the embodiment of the present invention includes a bonding step of peeling off the release sheet from the laminate obtained by the laminate manufacturing method and bonding an adherend onto the exposed thermal transfer layer via an adhesive layer. This bonding step makes it possible to obtain a bonded structure in which an adherend is bonded via an adhesive layer to at least a portion of the surface of the laminate on the thermal transfer layer side. As an example of a bonded structure, Figure 5 shows a bonded structure 500 in which a laminate having a thermal transfer layer 10 provided on the surface of a resin member 100 has an adherend 50 bonded to the surface of the thermal transfer layer 10 via an adhesive layer 40. Since the thermal transfer layer is formed using a sheet-like thermal transfer sheet rather than being applied to the surface of the resin member, it is possible to prevent unevenness due to repelling and the like. Therefore, the thermal transfer layer can be formed with a uniform thickness on the surface of the resin member, and the adhesive layer can be applied with a uniform film thickness. In addition, by providing a thermal transfer layer on the surface of a resin member in a molten state, the thermal transfer layer is fused and mixed by the heat of the surface of the resin member, and the adhesive strength between the thermal transfer layer and the resin member is high, so that the adhesive layer can be formed with good adhesion. Furthermore, when forming a joint structure, since the thermal transfer layer and the resin member can be integrally molded, a cleaning process using an organic solvent or a polishing process for removing the release agent before forming the adhesive layer is not required, which is safe and reduces the environmental burden and work load.

[0060] The adhesive contained in the adhesive layer is not particularly limited, and suitable adhesives such as acrylic, silicone, epoxy, phenol, polyurethane, cyanoacrylate, and polyamide adhesives can be used.

[0061] Examples of the adherends that constitute the joined structure include, but are not limited to, the thermosetting resins and thermoplastic resins used in the resin members described above, resin-based members made of FRP in which carbon fiber or glass fiber is impregnated with these resins, metal-based members such as iron, aluminum, titanium, copper, or alloys mainly made of these, inorganic members such as glass, tiles, concrete, and wood-based members such as wood.

[0062] <Thermal transfer sheet> Further, a thermal transfer sheet according to one embodiment of the present invention includes a release sheet and a thermal transfer layer, and the release sheet has no yield point and a breaking elongation of 100 to 600% in a stress-strain curve measured by a tensile test at Tα°C represented by the following formula (1). Tα℃ = glass transition temperature of release sheet (Tg)℃ + 70℃ (1) Since the thermal transfer sheet according to this embodiment has a sheet-like thermal transfer layer, it can be integrally molded by laying it on the surface of a member and heating it, rather than coating it on the surface of the member. Therefore, it is possible to prevent unevenness due to repelling and the like, and form a thermal transfer layer with a uniform thickness on the surface of the member. In addition, when applying the thermal transfer layer to a part of the surface of the member, it is possible to suppress a decrease in yield due to overflow and the like.

[0063] [Thermal transfer layer] For the thermal transfer layer in the thermal transfer sheet of this embodiment, the explanation for the thermal transfer layer in the thermal transfer sheet used in the above-mentioned method for producing a laminate can be directly applied.

[0064] [Release sheet] The release sheet in the thermal transfer sheet of this embodiment has no yield point and a breaking elongation of 100 to 600% in a stress-strain curve measured by a tensile test at Tα° C., represented by the following formula (1). Tα℃ = glass transition temperature of release sheet (Tg)℃ + 70℃ (1)

[0065] (Tensile test) The tensile test is carried out using a tensile tester equipped with a thermostatic chamber under the following test conditions. Test equipment: Shimadzu AG-X 200N Sample piece: Use a dumbbell No. 1 piece punched out. Tensile speed: 200mm / min Between marked lines: 40mm Pre-heating: Place the specimen between the chucks in a thermostatic chamber set at Tα°C, close the door, and once the temperature inside the chamber has stabilized (after approximately 10 minutes), begin the test.

[0066] (yield point) When a stress-strain curve is plotted using the above tensile test at Tα°C, with the horizontal axis representing elongation (%) and the vertical axis representing tensile stress (MPa), an inflection point usually appears as the sample transitions from the elastic region to the plastic region. At this time, a maximum point appears on the stress-strain curve, and the stress drops once and then rises again; this phenomenon is called the necking phenomenon, and this maximum point on the stress-strain curve is called the yield point. Here, when the release sheet does not have a yield point in the stress-strain curve measured by a tensile test at Tα° C., the local elongation of the release sheet during molding is suppressed, so that bending or tearing does not occur not only in the flat parts but also in the curved parts that tend to elongate locally, and the curved surface conformability is good. Therefore, the occurrence of wrinkles is effectively prevented not only in the flat parts but also in the curved parts.

[0067] (Elongation at break) In addition, in the stress-strain curve measured by the above tensile test at Tα° C., the point at which the release sheet breaks is taken as the breaking point, and the elongation value at that time is taken as the breaking point elongation. Here, when the elongation at break is 100 to 600%, uniform elongation is obtained, so that it becomes possible to follow a three-dimensional shape. If the elongation at break is less than 100%, the elongation is insufficient, so that wrinkles may occur or the sheet may break. If the elongation at break is more than 600%, there is a risk that a sufficient thickness of the thermal transfer layer cannot be obtained after molding. The elongation at break is preferably 110 to 500%, more preferably 120 to 400%, and even more preferably 150 to 400%. In one embodiment, the elongation at break may be 150 to 600%.

[0068] In addition, in the stress-strain curve measured by the above tensile test at Tα° C., the gradient of the plastic deformation region after 50% elongation from the inflection point between the elastic deformation region and the plastic deformation region of the release sheet is preferably 0 to 50. The inclination is preferably 0 to 50, since uniform elongation can be obtained over a wider range, and better three-dimensional conformability can be obtained. If the inclination is smaller than 0, localized elongation may occur. If the inclination is larger than 50, sufficient elongation may not be obtained during molding, and wrinkles may occur. The inclination is more preferably 5 to 40, and even more preferably 10 to 30. Here, since there is an inflection point when transitioning from the elastic region to the plastic region, the slope a can be calculated using the following formula (i), starting from the point 50% after the inflection point. a = ((S2-S1) / (E2-E1)) × 100 (i) E1: (inflection point growth +50) (%) E2: ((inflection point growth +50) +30)(%) S1: Stress (MPa) at (elongation at inflection point + 50) (%) S2: Stress (MPa) at ((elongation at inflection point + 50) + 30) (%)

[0069] In addition, the glass transition temperature (Tg) of the release sheet is determined by measuring the storage modulus and loss modulus, calculating the value of tan δ (E″ (loss modulus) / E′ (storage modulus)), and the peak temperature of tan δ on the low temperature side is defined as the glass transition temperature (Tg).

[0070] Examples of release sheets that can be used for the above thermal transfer sheet include unstretched polyamide 6, unstretched polyamide 66, biaxially oriented polyamide 6, biaxially oriented polyamide 66, biaxially oriented polypropylene, biaxially oriented polyethylene terephthalate, biaxially oriented polybutylene terephthalate, easily molded polyethylene terephthalate, cast molded polytetrafluoroethylene, unstretched extruded tetrafluoroethylene-ethylene copolymer (ETFE), unstretched extruded tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), unstretched extruded tetrafluoroethylene-hexafluoropropylene copolymer (FEP), and laminates having these as the main layer. From the viewpoints of ease of handling and prevention of breakage, the thickness of the release sheet is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 20 μm or more, and even more preferably 30 μm or more. From the viewpoint of conformability to a three-dimensional shape, the thickness is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 100 μm or less. If necessary, the surface of the release sheet facing the thermal transfer layer or both surfaces of the release sheet may be subjected to a release treatment using an appropriate release treating agent such as silicone.

[0071] In addition, a thermal transfer sheet according to another embodiment includes a release sheet and a thermal transfer layer, and the release sheet has no yield point and a breaking elongation of 100 to 600% in a stress-strain curve measured by a tensile test at a molding temperature Tβ°C in the lamination process.

[0072] [Production of thermal transfer sheet] The thermal transfer sheet can be manufactured by any suitable method. For example, a method of dipping a release sheet into a solution containing a material for the thermal transfer layer and a solvent (a composition for forming a thermal transfer layer) and then drying as necessary, a method of brushing a solution containing a material for the thermal transfer layer and a solvent on the surface of a release sheet and then drying as necessary, a method of applying a solution containing a material for the thermal transfer layer and a solvent on the surface of a release sheet using various coaters and then drying as necessary, a method of spraying a solution containing a material for the thermal transfer layer and a solvent on the surface of a release sheet and then drying as necessary, etc. can be mentioned.

[0073] The composition for forming the thermal transfer layer may be a solution in which the material for the thermal transfer layer is dissolved in a solvent. Examples of the solvent include water, alcohols such as methanol, ethanol, and isopropyl alcohol, ketones such as methyl ethyl ketone, esters, aliphatic, alicyclic, and aromatic hydrocarbons, halogenated hydrocarbons, amides such as dimethylformamide, sulfoxides such as dimethyl sulfoxide, and ethers such as dimethyl ether and tetrahydrofuran, and in order to suppress the formation of gelled matter, ethanol or a mixed solvent of ethanol and water is preferred. The solvent may be one type only or two or more types.

[0074] The solid content of the composition for forming the thermal transfer layer can be appropriately set depending on the purpose. From the viewpoint of thickness accuracy of the thermal transfer layer, the mass ratio is preferably 0.01 mass% to 20 mass%, more preferably 0.05 mass% to 10 mass%, and further preferably 0.1 mass% to 5 mass%.

[0075] The composition for forming the thermal transfer layer may contain various additives, as necessary, such as a pH adjuster, a crosslinking agent, a viscosity adjuster (e.g., a thickener), a leveling agent, a release adjuster, a plasticizer, a softener, a filler, a colorant (e.g., a pigment, a dye), a surfactant, an antistatic agent, a preservative, an antiaging agent, an ultraviolet absorber, an antioxidant, and a light stabilizer. For example, the addition of a colorant makes the thermal transfer layer visible, making it easier to determine whether the surface of the resin workpiece has already been modified, which is advantageous in terms of process control. The colorant may be, for example, a dye or a pigment, or may be a fluorescent material that is visible under black light.

[0076] [Laminate] A laminate according to an embodiment of the present invention includes the thermal transfer sheet and a resin member laminated on the thermal transfer layer side of the thermal transfer sheet. The laminate preferably includes a mixed layer in which a resin and the thermal transfer layer are mixed between the resin member and the thermal transfer layer.

[0077] The above descriptions can be applied to the thermal transfer sheet, the thermal transfer layer, and the resin member.

[0078] The mixed layer is a layer in which the resin and the thermal transfer layer are mixed, for example, by providing a thermal transfer layer on at least a part of the surface of the resin member and performing heat welding or heat adhesion, the interface between the thermal transfer layer and the resin member is melted and contacted, and the mixed layer is obtained by the heat welding. The formation of the mixed layer improves the adhesive strength between the resin member and the thermal transfer layer. In the mixed layer, it is preferable that the resin and the thermal transfer layer are bonded by a chemical reaction such as a covalent bond. The interface between the resin member and the thermal transfer layer disappears due to a chemical reaction such as a covalent bond, and the resin member and the thermal transfer layer are integrated, thereby obtaining a better adhesive strength.

[0079] The thickness of the mixed layer can be appropriately determined depending on the heat welding conditions, the type of resin contained in the resin member, and the type of the thermal transfer layer. The thickness of the mixed layer is preferably 1.5 nm or more, and more preferably 2.0 nm or more.

[0080] In the laminate according to the embodiment of the present invention, the thickness of the thermal transfer layer is preferably 0.001 μm to 20 μm, more preferably 0.01 μm to 15 μm, still more preferably 0.5 μm to 10 μm, and particularly preferably 0.7 μm to 10 μm. EXAMPLES

[0081] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples in any way.

[0082] Example 1 (Thermal transfer sheet) (Lead City Corporation, Fine Resin FR-105 (methoxymethylated polyamide resin) / Toa Gosei Co., Ltd., ARUFON (registered trademark) UC-3000 (carboxyl group-containing acrylic oligomer) (mass ratio 100 / 2 mixture)) was dissolved in a mixed solvent of ethanol (EtOH) / water / isopropanol (IPA) = 60 mass % / 10 mass % / 30 mass % at 60°C to prepare a 20 mass % solution (composition for forming a thermal transfer layer). The composition for forming the thermal transfer layer thus prepared was filtered through a nylon mesh with an opening of 188 μm, and then coated onto a release sheet (OT-P2171: biaxially oriented polypropylene film (OPP) manufactured by Toyobo Co., Ltd., thickness 30 μm) using a bar coater. After air drying, it was further dried at 100°C for 1 minute in a thermostatic dryer to prepare a thermal transfer sheet having a thermal transfer layer on the release sheet.

[0083] <Glass transition temperature (Tg)> The storage modulus and loss modulus of the release sheet were measured, the value of tan δ (E″ (loss modulus) / E′ (storage modulus)) was calculated, and the peak temperature of tan δ on the low temperature side was determined as the glass transition temperature (Tg).

[0084] <Melting point (Tm)> The storage modulus and loss modulus of the release sheet were measured, the value of tan δ (E″ (loss modulus) / E′ (storage modulus)) was calculated, and the peak temperature of tan δ on the high temperature side was taken as the melting point (Tm). The melting point (T1) of the thermoplastic resin was also measured in the same manner. In addition, since amorphous resins do not have a melting point, the decomposition temperature was regarded as the melting point.

[0085] (Measurement of storage modulus and loss modulus) The release sheet was cut into a strip of 10 mm length (measurement length) × 5 mm width with a cutter knife, and the storage modulus / loss modulus was measured at 25 to 500°C using a solid viscoelasticity measuring device (RSAIII, manufactured by TA Instruments, Inc.) The measurement conditions were a frequency of 1 Hz and a heating rate of 5°C / min.

[0086] (Tensile test) A tensile test was performed on the release sheet under the following test conditions using a tensile tester equipped with a thermostatic chamber, and the presence or absence of a yield point in the stress-strain curve, the elongation at break, and the slope of the plastic deformation region after 50% elongation from the inflection point between the elastic deformation region and the plastic deformation region were measured or calculated. Test equipment: Shimadzu AG-X 200N Sample piece: A dumbbell No. 1 piece punched out was used. Tensile speed: 200mm / min Between marked lines: 40mm Pre-heating: In a thermostatic chamber set at the molding temperature Tβ℃ or Tα℃ expressed by the following formula (1), the sample piece was placed between the chucks, the door was closed, and the test was started after the temperature inside the chamber had stabilized (approximately 10 minutes had passed). Tα℃ = glass transition temperature of release sheet (Tg)℃ + 70℃ (1)

[0087] <Thickness of thermal transfer layer> The thickness of the thermal transfer layer was measured with a dial gauge (GC-9 manufactured by Peacock). The thickness of the thermal transfer sheet was measured, and the thickness of the release sheet from which the thermal transfer layer was removed was measured, and the difference was taken as the thickness of the thermal transfer layer. The average thickness was the average value of measurements at 10 points. The unit of thickness in the table is μm.

[0088] (Laminate (1)) The thermal transfer layer side of the thermal transfer sheet prepared above was placed on a twill carbon fiber reinforced thermosetting epoxy resin (C-EpTS) (width 200 mm × length 200 mm × thickness 2 mm) as a resin member, and pressed at the molding temperature Tβ℃ shown in Table 1 to produce a flat laminate (1).

[0089] (joint structure) Two of the laminates (1) (laminates 500) prepared above were bonded in the form of FIG. 6 using an adhesive sheet 600 so that the thermal transfer layer sides of each were bonded together after the release sheets of each were peeled off, to form a bonded structure. The adhesive sheet used was a rubber-modified epoxy adhesive sheet described in JP 2012-197427 A. The adhesive area was 25 mm x 10 mm. The adhesive curing conditions were 150°C x 20 minutes.

[0090] <Shear adhesive strength evaluation> The tensile shear adhesive strength between the two laminated members in the bonded structure was measured using a tensile tester (manufactured by Minebea, model number: TG-100kN). The measurements were performed at 25°C and a tensile speed of 5mm / min. The measured value was converted per unit area to obtain the shear adhesive strength.

[0091] (painted items) After peeling off the release sheet of the laminate (1) prepared above, the thermal transfer layer was spray-painted with "Body Pen" acrylic paint (for automobiles) manufactured by Soft99 Corporation, and dried at room temperature for one day and one night to produce a coated product with a coating film having a thickness of 50 μm.

[0092] <Paint adhesion evaluation> The coated object was cut into a strip of approximately 4 mm width and a cross-cut evaluation was carried out using the cross-cut method described in JIS K5600-5-6 to evaluate the coating adhesion. Cutting distance: 2mm Crosscut quantity: 100 squares Peeling tape: (Nichiban) cellophane tape 24mm wide

[0093] (Laminate (2)) In order to evaluate the appearance defect due to wrinkles caused by the release sheet, a laminate (2) was formed using a mold shaped like a smartphone housing. Specifically, the thermal transfer layer side of the thermal transfer sheet prepared above was placed on top of a twill carbon fiber reinforced thermosetting epoxy resin (C-EpTS) (width 100 mm x length 170 mm x thickness 1 mm) as a resin member, and laminate (2) was produced by pressing in a mold at the molding temperature Tβ℃ shown in Table 1. The size of the smartphone case was 70 mm wide x 140 mm long, and the corners of the case had a radius of curvature R = 5 mm in the height direction, a radius of curvature R = 5 mm in the planar direction, and a draw depth of 10 mm.

[0094] <Appearance evaluation> The appearance of the laminate (2) in planar shape and curved shape was visually observed and evaluated according to the following criteria. Regarding the appearance in plan view, those in which wrinkles were formed on the flat portion of the laminate (2) due to the release sheet were marked with "X", and those which could be molded without wrinkles were marked with "O". Regarding the appearance of the curved shape, the laminate (2) was marked with an X when wrinkles were formed at the corners of the laminate due to the release sheet, and when there were no wrinkles but the release sheet was torn, or when thinning or breakage occurred at the lower part of the side due to local stretching of the release sheet. The laminate was marked with an O when it was able to be molded without wrinkles. Regarding pinholes, if even one void-like appearance defect was found, it was judged as ×, and if no pinholes were found, it was judged as ◯.

[0095] [Examples 2 to 16, Comparative Examples 3 to 5] Except for changing the thermal transfer layer, release sheet, resin member, and molding temperature Tβ℃ as shown in Tables 1 and 2, the thermal transfer sheet, laminate (1), bonded structure, coated object, and laminate (2) were prepared in the same manner as in Example 1, and each measurement and evaluation was performed in the same manner as in Example 1. Note that Example 1 and Examples 5 to 7 have different thicknesses of the thermal transfer layer. Also, Example 1 and Example 8 use the same thermal transfer sheet, but the forming temperatures Tβ°C are different. Also, Example 3 and Example 10 use the same thermal transfer sheet, but the forming temperatures Tβ°C are different. Also, Example 4 and Example 9 use the same thermal transfer sheet, but the forming temperatures Tβ°C are different. Also, Examples 12 to 14 use the same thermal transfer sheet, but the forming temperatures Tβ°C are different.

[0096] <Thermosetting resin curing temperature (T2)> 5 mg of the thermosetting resin before hardening was cut out and subjected to DSC (differential scanning calorimetry) measurement. Equipment: TA Instruments high-sensitivity DSC Q2000 Atmosphere gas: N2 (50ml / min) Heating rate: 2℃ / min ·Temperature conditions: -30℃→300℃ The peak temperature of the heat generation curve accompanying curing when the measurement was performed under the above conditions was taken as the curing temperature (T2).

[0097] [Comparative Examples 1-2] In Comparative Examples 1 and 2, the thermal transfer sheet was not provided with a thermal transfer layer, and the release sheet was placed on a resin member and pressed. Thereafter, the release sheet was removed, and a bonded structure was produced in the same manner as in Example 1 using the resin member after the press process that did not have a thermal transfer layer, and a shear adhesive strength evaluation was performed. In addition, a pressed resin part that did not have a thermal transfer layer was directly sprayed with "Body Pen" acrylic paint (for automobiles) manufactured by Soft99 Corporation to produce a painted object with a coating film of 50 μm thickness, and the paint adhesion was evaluated. In addition, the thermal transfer sheet was placed on a resin member without providing a thermal transfer layer, using the release sheet as it was, and molded in a mold for a smartphone housing, and the appearance was evaluated.

[0098] The evaluation results of Examples 1 to 16 and Comparative Examples 1 to 5 are shown in Tables 1 and 2 below.

[0099] FIG. 7 shows the stress-strain curve of the release sheet of Example 2 measured by a tensile test at a molding temperature of Tβ° C. As shown in Figure 7, this stress-strain curve does not have a yield point. The elongation at break is 357%. Furthermore, since there is an inflection point when moving from the elastic region to the plastic region, the slope a of the plastic deformation region after 50% elongation from the inflection point between the elastic deformation region and the plastic deformation region is calculated as 13.7 using the following formula (i) starting from the point 50% after the inflection point, because an inflection point exists when moving from the elastic region to the plastic region. a = ((S2-S1) / (E2-E1)) × 100 (i) E1: (inflection point growth +50) (%) E2: ((inflection point growth +50) +30)(%) S1: Stress (MPa) at (elongation at inflection point + 50) (%) S2: Stress (MPa) at ((elongation at inflection point + 50) + 30) (%)

[0100] FIG. 8 shows the stress-strain curve of the release sheet of Comparative Example 5 measured by a tensile test at a molding temperature of Tβ° C. As shown in Figure 8, this stress-strain curve has a yield point. The elongation at break is 580%. Furthermore, the slope a of the plastic deformation region after 50% elongation from the inflection point between the elastic deformation region and the plastic deformation region is 0.3.

[0101] [Table 1]

[0102] [Table 2]

[0103] The release sheets listed in the table are as follows. OT-P2171: Biaxially oriented polypropylene film (OPP) manufactured by Toyobo Co., Ltd. V-01: Unstretched polyamide 6 film (PA6) manufactured by Xiamen Xinwang New Materials Technology Co., Ltd. R-08: Unstretched polyamide 66 film (PA66) manufactured by Xiamen Xinwang New Materials Technology Co., Ltd. CF200: Cast polytetrafluoroethylene film (cast PTFE) manufactured by Textiles Coated International ETFE MR: Textiles Coated International, Inc. Unstretched extruded ethylene-tetrafluoroethylene copolymer film (unstretched ETFE) MRF: Mitsubishi Chemical Corporation biaxially oriented polyethylene terephthalate film (PET) / silicone treatment) Niftron No. 900UL: Cut-molded polytetrafluoroethylene film (cut PTFE) manufactured by Nitto Denko Corporation G930E50: Easy-to-form polyethylene terephthalate (easy-to-form PET) manufactured by Mitsubishi Chemical Corporation G980E50: Easy-to-form polyethylene terephthalate (easy-to-form PET) manufactured by Mitsubishi Chemical Corporation TPX 88BMT4: Unstretched polymethylpentene film (PMP) manufactured by Mitsui Chemicals, Inc. FMN-50WD: Fujiko Co., Ltd. Biaxially oriented polyethylene terephthalate film (PET / silicone treatment) For MRF and FMN-50WD, a thermal transfer layer was applied to the silicone-treated surface. For OT-P2171, CF200, ETFE MR, Niftron No. 900UL, and TPX 88BMT4, the thermal transfer layer was applied in an untreated state. The other release sheets were silicone-treated on one side, and the thermal transfer layer was applied to the silicone-treated surface.

[0104] The resin members listed in the table are as follows. C-EpTP: Unidirectional long carbon fiber reinforced thermoplastic epoxy resin C-EpTS: Twill carbon fiber reinforced thermosetting epoxy resin

[0105] In Examples 1 to 16, the release sheet had no yield point in the tensile test and had a breaking elongation in the range of 100 to 600%, so that the appearance of the laminate was good, and the thermal transfer layer was firmly attached to the resin member, and a uniform and smooth thermal transfer layer was formed. Therefore, a coated object with good coating adhesion and a bonded structure with good adhesion were obtained. In contrast, in Comparative Examples 1 and 2, although the release sheets had the specified stress-strain curves, good paint adhesion and bonding properties were not obtained because there was no thermal transfer layer. In Comparative Example 3, the release sheet did not have a yield point in the tensile test, but the elongation at break was small, so wrinkles and tears occurred at the corners. In Comparative Examples 4 and 5, the release sheets had a yield point in the tensile test, so that local elongation occurred and the release sheets became thin below the corners, causing wear. [Explanation of symbols]

[0106] 10 Thermal transfer layer 20 Release sheet 30 Paint film 40 Adhesive layer 50 Adherent 100 Resin material 200 Thermal transfer sheet 300 Painted items 400 Jointed structure 500 laminate 600 Adhesive Sheet

Claims

1. A method for producing a laminate, comprising: a lamination step of laminating a thermal transfer layer side of a thermal transfer sheet having a release sheet and a thermal transfer layer to at least a part of a surface of a resin member by heat adhesion, The release sheet has no yield point and a breaking elongation of 100 to 600% in a stress-strain curve measured by a tensile test at a molding temperature Tβ°C in the lamination step; The release sheet is at least one selected from unstretched polyamide 6, unstretched polyamide 66, biaxially oriented polyamide 6, biaxially oriented polyamide 66, biaxially oriented polypropylene, cast molded polytetrafluoroethylene, unstretched extruded tetrafluoroethylene-ethylene copolymer (ETFE), unstretched extruded tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), unstretched extruded tetrafluoroethylene-hexafluoropropylene copolymer (FEP), and laminates having these as main layers.

2. 2. The method for producing a laminate according to claim 1, wherein the release sheet has no yield point and a breaking elongation of 150 to 600% in a stress-strain curve measured by a tensile test at a molding temperature Tβ ° C. in the lamination step.

3. 3. The method for producing a laminate according to claim 1 or 2, wherein in a stress-strain curve measured by a tensile test at the forming temperature Tβ ° C, the release sheet has a slope of a plastic deformation region after 50% elongation from an inflection point between an elastic deformation region and a plastic deformation region of 0 to 50.

4. The method for producing a laminate according to any one of claims 1 to 3, wherein the thermal transfer layer has an average thickness of 0.1 µm to 50 µm.

5. The method for producing a laminate according to any one of claims 1 to 4, wherein in the lamination step, the heat bonding is carried out by hot pressing.

6. A method for producing a coated article, comprising a coating film forming step of peeling the release sheet from the laminate obtained by the method for producing a laminate according to any one of claims 1 to 5, and forming a coating film on the exposed thermal transfer layer.

7. A method for producing a bonded structure, comprising a bonding step of peeling off the release sheet from the laminate obtained by the method for producing a laminate according to any one of claims 1 to 5, and bonding an adherend onto the exposed thermal transfer layer via an adhesive layer.

8. A release sheet and a thermal transfer layer are provided, The release sheet has no yield point and a breaking elongation of 100 to 600% in a stress-strain curve measured by a tensile test at Tα ° C. represented by the following formula (1), The release sheet is a thermal transfer sheet which is at least one selected from unstretched polyamide 6, unstretched polyamide 66, biaxially oriented polyamide 6, biaxially oriented polyamide 66, biaxially oriented polypropylene, cast molded polytetrafluoroethylene, unstretched extruded tetrafluoroethylene-ethylene copolymer (ETFE), unstretched extruded tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), unstretched extruded tetrafluoroethylene-hexafluoropropylene copolymer (FEP), and laminates having these as main layers. Tα°C = glass transition temperature of release sheet (Tg)°C + 70°C (1)

9. The thermal transfer sheet according to claim 8, wherein the release sheet has no yield point and has a breaking elongation of 150 to 600% in a stress-strain curve measured by a tensile test at Tα ° C. represented by the formula (1).

10. The thermal transfer sheet according to claim 8 or 9, wherein in a stress-strain curve measured by a tensile test at Tα°C, the slope of the plastic deformation region after 50% elongation from the inflection point between the elastic deformation region and the plastic deformation region is 0 to 50.

11. The thermal transfer sheet according to any one of claims 8 to 10, wherein the thermal transfer layer has an average thickness of 0.1 µm to 50 µm.

12. The thermal transfer sheet according to any one of claims 8 to 11, wherein the thermal transfer layer contains a polymer component, and the polymer component contains at least one of a polymer having a non-polar unit and a polar unit, and a polymer in which a portion of a polymer composed of a non-polar unit is modified with a polar unit having a polar group.

13. The thermal transfer sheet according to claim 12, wherein the polymer component contains at least one selected from the group consisting of a methoxymethyl group-containing polymer, a hydroxyl group-containing polymer, a carboxyl group-containing polymer, and an amino group-containing polymer.

14. The thermal transfer sheet according to any one of claims 8 to 13, which is for application by heating.

15. A thermal transfer sheet according to any one of claims 8 to 14, a resin member laminated on the thermal transfer layer side of the thermal transfer sheet.

16. The laminate according to claim 15 , wherein the resin member is a prepreg.

Citation Information

Patent Citations

  • Primer for polyphenylene sulfide and bonding

    JP2000226536A

  • Laminated film for transfer foil and transfer foil using it

    JP2007136699A

  • Surface protective polyester film for molding

    JP2008088410A

  • Polyester film

    JP2010070581A

  • Laminated film with high mold releasability

    JP2011173298A